Analysis of Customer Satisfaction of Mayasari Bakti Buses in Jabodetabek - Samaatan, Nuriyati; Ginting, Selamat; Robingah; Firmansyah, Jun; Saputra, Haryo Bimo (Siber Journal of Advanced Multidisciplinary, 2025)
This research aims to analyze the influence of public relations as variable X1, service quality as variable X2, and customer satisfaction as variable Y on cosumers of Mayasari Bakti bus in Jabodetabek. This is quantitative research using probability sampling, specifically purposive sampling. Determination of margin of error using the Slovin formula with a margin of error of 10% and 100 respondents. Data was analyzed using SPSS. The margin of error was determined using the Slovin formula with a 10% error rate and 100 respondents. Data were analyzed using SPSS. The research found that the influence of Public Relations on customer satisfaction of Mayasari Bakti transportation services is 0.811, indicating that variable X1 influences customer satisfaction with Mayasari Bakti Bus services. Service Quality as variable X2 yields a value of 0.886, and the Information Needs variable yields a value of 0.879. It can be concluded that both variables X1 and X2 influence variable Y.